1999
DOI: 10.1128/jb.181.21.6730-6738.1999
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cytochrome c Oxidase Activity and Acquisition of Resistance to Quinone Analogs in a Laccase-Positive Variant of Azospirillum lipoferum

Abstract: Laccase, a p-diphenol oxidase typical of plants and fungi, has been found recently in a proteobacterium, Azospirillum lipoferum. Laccase activity was detected in both a natural isolate and an in vitro-obtained phase variant that originated from the laccase-negative wild type. In this study, the electron transport systems of the laccase-positive variant and its parental laccase-negative forms were compared. During exponential (but not stationary) growth under fully aerobic (but not under microaerobic) condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 53 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Azospirilla possess an oxidative type of metabolism, and have a complex branched electron transport system (Alexandre et al, 1999) that is likely to generate ROS during normal metabolic function. Azospirilla grow best under conditions of low oxygen concentrations, which they seek primarily by aerotaxis (Barak et al, 1982;Zhulin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Azospirilla possess an oxidative type of metabolism, and have a complex branched electron transport system (Alexandre et al, 1999) that is likely to generate ROS during normal metabolic function. Azospirilla grow best under conditions of low oxygen concentrations, which they seek primarily by aerotaxis (Barak et al, 1982;Zhulin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial laccase was first reported in Azospirillum lipoferum (Givaudan et al, 1993); it plays a role in cell pigmentation, oxidation of phenolic compounds (Faure et al, 1994(Faure et al, , 1995 and/or electron transport (Alexandre et al, 1999). Bacterial protein sequence studies have indicated that the laccases are represented by high G+C Gram positive bacteria and α-, γand ε-proteobacteria (Alexandre and Zhulin, 2000); as have been shown in Bacillus sp., Streptomyces sp., and a γ proteobacterium (Bains et al, 2003;Sharma et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Bacterial cells must have a strategy to cope with the intracellular presence of laccase due to its possible toxic byproducts. Rearrangement of the electron transport system has been suggested as a way in which the laccase-positive cells adapt to endogenous reactive quinones generated by laccases [102]. However, the extracellular localization of laccase is demonstrated in some bacilli and filamentous actinomycetes [103,104].…”
Section: Bacterial Laccasesmentioning
confidence: 99%
“…In general, laccase corresponding gene products are mainly involved in metal homeostasis/oxidation, sporulation, morphogenesis, and cell and spore pigmentation and are linked to resistance to different stresses. The Azospirillum laccase was reported to be involved in cell pigmentation [85], utilization of naturally occurring plant phenolic compounds resulting from lignin metabolism [123], and/or electron transport [102]. These capabilities could be related to the competitiveness of Azospirillum sp.…”
Section: Bacterial Laccasesmentioning
confidence: 99%